Extracellular superoxide dismutase (ecSOD) in vascular biology: an update on exogenous gene transfer and endogenous regulators of ecSOD - QIN, ZHENYU (Transl Res, 2007)
Extracellular superoxide dismutase (ecSOD) is the major extracellular scavenger of superoxide ( [Formula: see text]) and a main regulator of nitric oxide (NO) bioactivity in the blood vessel wall, heart, lungs, kidney, and placenta. Involvement of [Formula: see text] has been implicated in many pathological processes, and removal of extracellular [Formula: see text] by ecSOD gene transfer has emerged as a promising experimental technique to treat vascular disorders associated with increased oxidant stress. In addition, recent studies have clarified mechanisms that regulate ecSOD expression, tissue binding, and activity, and they have provided new insight into how ecSOD interacts with other factors that regulate vascular function. Finally, studies of a common gene variant in humans associated with disruption of ecSOD tissue binding suggest that displacement of the enzyme from the blood vessel wall may contribute to vascular diseases. The purpose of this review is to summarize recent research findings related to ecSOD function and gene transfer and to stimulate other investigations into the role of this unique antioxidant enzyme in vascular pathophysiology and therapeutics.